Correction to: Feminisation of the health workforce and wage conditions of health professions: an exploratory analysis - Geordan Shannon; Nicole Minckas; Des Tan; Hassan Haghparast-Bidgoli; Neha Batura; Jenevieve Mannell (BMC, 2019)
The original article [1] contained an error in the presentation of all figures and tables; each figure and table is now set out and designated appropriately in the original article.